ANCA-Associated Vasculitis Co-Occurrence With Systemic Sclerosis: A Case Report of a Rare Diagnostic Dilemma. (26th June 2018) - Cheta, Jordana; Binder, Michael; Kowalewska, Jolanta; Magoon, Sandeep
Systemic sclerosis (SSc) is a rare autoimmune disorder that is typically divided into limited cutaneous systemic sclerosis and diffuse cutaneous systemic sclerosis. Scleroderma renal crisis (SRC) is a severe complication of SSc and typically presents with new-onset hypertension and a reduction in renal functioning. In patients presenting with typical features of SRC, treatment with an angiotensin-converting enzyme inhibitor along with dialysis as needed is typically initiated empirically. Renal biopsy is not recommended in patients with SSc presenting with typical features of SRC. Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a rare co-occurrence with SSc, in around 2.5% to 9% of patients. AAV is an inflammatory condition that can result in renal failure due to mononuclear cell infiltration and destruction of blood vessels. Treatment of AAV is drastically different from SRC and typically consists of immunosuppressants and dialysis if needed. SRC and AAV can only reliably be distinguished by renal biopsy. We present a rare case of a 70-year-old female with limited cutaneous systemic sclerosis who presented to the emergency department with new-onset renal failure. Her serology was found to be positive for antinuclear antibodies and myeloperoxidase antibodies, resulting in a renal biopsy, which revealed an acute necrotizing vasculitis consistent with AAV. We suggest consideration of a renal biopsy in patients with SSc who present with new-onset renal failure, especially with nonresponse to SRC treatment or positive serology.